Securitization: An alternative funding mechanism for the microfinance institutions / Shahadat Hossain and Rubaiyet Hasan Khan - Hossain, Shahadat; Hasan Khan, Rubaiyet (Faculty of Business and Management ; UiTM Press, 2018)
Despite microfinance has been widely appreciated as an informal financial mechanism to provide financial services to the poor people in developing countries, this sector is still lacking behind in fulfilling the demand gap due to the dearth of adequate funds. Securitization opens a new horizon that overcomes the funding barriers of microfinance through which the top tier Microfinance Institutions (MFIs) can accumulate funds to enlarge their portfolio without issuing any debt or equity. This paper is a desk study that synthesizes how securitization can be used in the funding of the MFI portfolio and what are the benefits and risks associated with securitization of microfinance portfolio. As a case study, we use the two examples of cross-border securitizations in the microfinance industry to diagnose the role of securitization in microfinance